The Effect of Bullying and Work Discipline on Employee Productivity with Compensation as an Intervening Variable at Cipta Indah Group Merauke - Johansyah, Nicholas; Ariadi, Wa; Meliala, Janita S. (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study is entitled The Effect of Bullying and Work Discipline on Employee Productivity with Compensation as an Intervening Variable at Cipta Indah Group Merauke. The aim is to determine and analyze whether bullying and work discipline have a positive and significant effect directly or indirectly through compensation on productivity at PT CIG Group. The number of samples used was 108 employees. The data analysis used is Partial Least Square (PLS) regression to test the hypotheses proposed in the study. The results of this study indicate that the direct effect of bullying and compensation on work productivity shows an insignificant effect. As for the direct effect of work discipline and work productivity, it has a significant effect. As for the direct effect of bullying and work discipline on compensation, it shows a significant influence and relationship. For the results of the indirect effect of the variables of bullying and work discipline on productivity with compensation as an intervening variable, it shows that compensation is not able to mediate or cannot be a mediator for bullying and work discipline.